Deconstructing the Meaning of Structural Da'wah: A Study of the Safari Subuh Berjama’ah by the Government of Ponorogo Regency - Mochammad Irfan Achfandhy (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2021)
Safari Subuh Berjama'ah is a structural da'wah effort carried out by the Ponorogo Regency Government to suppress people's immorality behavior. However, religious and political relations in the form of structural da'wah continue to be debated. The purpose of this study was to elaborate on the motives of political interests in the structural da'wah framework of Safari Subuh Berjama'ah. The research method used a descriptive qualitative approach. The approach used is a narrative approach by analyzing the text to deconstruct the da'wah motive from the news on the online media portal. The results showed that the purpose of the Safari Subuh Berjama'ah is to increase religiosity, build brotherhood bonds and village views as an effort to find out the development and problems of society. But on the other hand, there is a hidden motive behind the activity, which is to use it as a method of political communication to gain popular votes or campaigns. Uncompetitive political and religious relations tend to be more dominant in the political element. So that the values of da'wah which should be oriented towards Islamic teachings have shifted contradictory to the interests of politicians.Keyword: Structural Da'wah, Deconstruct, Political.